2006
DOI: 10.4103/0019-5278.27301
|View full text |Cite
|
Sign up to set email alerts
|

Work-related health problems in salt workers of Rajasthan, India

Abstract: Article W W W W Work-r ork-r ork-r ork-r ork-related health pr elated health pr elated health pr elated health pr elated health problems in salt workers oblems in salt workers oblems in salt workers oblems in salt workers oblems in salt workers of Rajasthan, India of Rajasthan, India of Rajasthan, India of Rajasthan, India of Rajasthan, India Abstract Background: About 20,000 men and women are engaged in the production of salt in Rajasthan alone, which is an important unorganized sector. The salt workers are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
2
7
2
Order By: Relevance
“…2 Only few studies have been conducted to assess the health status and KAP among salt workers. [2][3][4][5][6] In a study involving 205 salt workers in Rajasthan, it was found that the brine (concentrated salt water) workers had a fair knowledge of occupational health problems (98.7%) and protective measures (100%) as compared to non-brine workers for whom these figures were 89% and 85.8% respectively. 4 In our study, both brine and nonbrine workers were taken together as all of them were involved in both brine and non-brine work of salt production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Only few studies have been conducted to assess the health status and KAP among salt workers. [2][3][4][5][6] In a study involving 205 salt workers in Rajasthan, it was found that the brine (concentrated salt water) workers had a fair knowledge of occupational health problems (98.7%) and protective measures (100%) as compared to non-brine workers for whom these figures were 89% and 85.8% respectively. 4 In our study, both brine and nonbrine workers were taken together as all of them were involved in both brine and non-brine work of salt production.…”
Section: Discussionmentioning
confidence: 99%
“…It is also evident from the review of literature that there are very few studies on salt workers. [3][4][5][6] This paper is on knowledge, attitude and practices regarding their work related hazards as well as the availability and use of Personal protective equipments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies had also shown that the workers of the electronics industries had suffered from visual discomforts (10). The workers engaged in salt production experienced visual problems such as eye redness, glare sensitivity, watery eyes, burning eyes, dimness of vision and photophobia (14). Jewellery manufacturing activity involves precision designs, setting the metal as well as the stones, polishing and filing.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the salt workers suffered from ophthalmic problems. However the prevalence of hypertension was 12.0% [6]. Case control study conducted by NIOH (National Institute of Occupational Health) on 2104 subjects of which including 1549 salt workers working at different salt sites in the little Rann of Kutch and 555 control subjects from the nearby villages suggested that the prevalence of skin and eye symptoms were significantly higher among the salt workers.…”
Section: Impact Of Salt Work On Worker's Healthmentioning
confidence: 99%